The Influence of Learning Motivation and Learning Facilities on The Learning Presetation of Mambaul Ulum Mts Mambaul Ulum Mts Students Margo Mulyo Belitang 2 Oku Timur - Maulana, Habib; Apriyanty, Diny Nur; Arif, Fathul; Miftakhurrohmah, Miftakhurrohmah; María-José, Chandrasekaran (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The purpose of this study was to determine whether there is an effect of learning motivation and social studies learning facilities either partially or simultaneously on social studies learning achievement. The population of this study were students of class VII A and VII B of MTS MAMBAUL ULUM Margo Mulyo Belitang 2 Oku Timur, whose number was 56. The variables studied were learning motivation and learning facilities as independent variables and learning achievement as related variables. The data collection method uses direct observation at school. The results of this study indicate 1) there is an effect of learning motivation on learning achievement, 2) there is an influence of learning facilities on learning achievement 3) there is a simultaneous influence of learning motivation and learning facilities on social studies learning achievement.